Distribusi Kewenangan Pusat Dan Daerah Dalam Bingkai Otonomi Daerah Di Indonesia - Arifin, Firdaus (Universitas Sang Bumi Ruwa Jurai, 2024)
In a state government administration system that uses the principle of distribution of power or what is known as decentralization, namely that authority is distributed to regional governments at each level, this gives rise to a model of regional government that requires autonomy in the exercise of authority. The division of the Unitary State of the Republic of Indonesia into provinces, districts and cities, as well as the division of government affairs between the Central Government and Regional Governments, of course gives rise to authority and financial relations. This research is normative juridical research so that data is collected in the literature, the data that has been obtained is then analyzed qualitatively juridically. The research resulted in the conclusion that in Law Number 23 of 2014 concerning Regional Government, the relationship between the central government and regional governments in Indonesia is to use the concept of the relative autonomy model, the central government still needs to uphold the principle of regional autonomy as mandated by the constitution. Meanwhile, in terms of regional government financial relations, it is appropriate to manage and use balance funds in an accountable, transparent and professional manner